Tracking temporal shifts of peripheral blood NLR, PLR, and ALB: a prognostic tool for PD-1 inhibitor efficacy in advanced malignant melanoma - Deng, Yushu; Han, Yikai; Meng, Xiangrui; Pei, Jiaxin; Yang, Mengmeng; Xiao, Ziyi; Wang, Feng; Lu, Taiying (Frontiers in Oncology, 2026)
ObjectivePD-1 monoclonal antibodies are cornerstone therapies for advanced malignant melanoma, yet treatment response varies greatly between patients. This study investigated temporal changes in peripheral blood inflammatory and nutritional parameters during PD-1 therapy, examined their associations with clinical outcomes, and identified prognostic biomarkers.MethodsA retrospective analysis was conducted on 99 patients with advanced malignant melanoma who received PD-1 monoclonal antibody treatment at the First Affiliated Hospital of Zhengzhou University (January 2019–September 2024). Imaging evaluations (CT/MRI, with PET-CT for suspected distant metastasis) were performed at baseline (T0, before treatment), the end of the 2nd cycle (T2), and the end of the 4th cycle (T4) to assess treatment response per the immune-related Response Evaluation Criteria in Solid Tumors (irRECIST).After four treatment cycles, patients were stratified into a clinical benefit group (complete response [CR] + partial response [PR] + stable disease [SD], n=68) and a non-benefit group (progressive disease [PD], n=31) based on the immune-related Response Evaluation Criteria in Solid Tumors (irRECIST). Peripheral blood samples were collected at five time points: baseline (T0), post-first cycle (T1), post-second cycle (T2), post-third cycle (T3), and post-fourth cycle (T4). Dynamic changes in neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), systemic immune-inflammation index (SII), serum albumin (ALB), and prognostic nutritional index (PNI) were compared between groups. Line graphs and box plots were used to visualize indicator trends, while logistic regression and receiver operating characteristic (ROC) curves were applied to evaluate prognostic value.ResultsNon-benefit patients showed NLR peaks at T2 and PLR peaks at T1, while benefit patients had stable levels. ALB and PNI were higher and stable in the benefit group (P<0.05). A model combining T1PLR, T1ALB, and T2NLR achieved an AUC of 0.89 (sensitivity 0.90, specificity 0.79).ConclusionDynamic monitoring of peripheral blood NLR, PLR, and ALB provides critical insights for predicting PD-1 immunotherapy efficacy in patients with advanced malignant melanoma. These indicators hold promise as potential clinical biomarkers to guide the development of individualized treatment strategies.